Urgency of regulating Cyberbullying on Indonesian law - Eka Nugraha Putra (Proceedings of AICS - Social Sciences, 2013)
In the delevopment of telematics, Indonesia is one of the country which affected by and also give freedom of speech and freedom of expression. But the freedom of expression are not balanced with the ethical of internet using. One of the example is Cyberbullying. With the development of technology and freedom in the internet, Bullying has become Cyberbullying which is become more complicated. Cyberbullying basically can affected to everyone, but in some cases teenager are often become victim, especially girl. This paper will try to review and analyse regulation of Cyberbullying in the Indonesian Law, are the regulation could accomodate Cyberbullying as a part of cybercrime, or the regulation need to be revised in order to regulate Cyberbullying.Keywords: Cybercrime, Cyberbullying.